2017
DOI: 10.1177/0271678x17746132
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium induces preconditioning of the neonatal brain via profound mitochondrial protection

Abstract: Magnesium sulphate (MgSO) given to women in preterm labor reduces cerebral palsy in their offspring but the mechanism behind this protection is unclear, limiting its effective, safe clinical implementation. Previous studies suggest that MgSO is not neuroprotective if administered during or after the insult, so we hypothesised that MgSO induces preconditioning in the immature brain. Therefore, we administered MgSO at various time-points before/after unilateral hypoxia-ischemia (HI) in seven-day-old rats. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 67 publications
(86 reference statements)
5
45
0
1
Order By: Relevance
“…Additionally, the serum Mg 2+ concentrations measured in both models 3 h post injection were within the therapeutic window (2–4 mmol/L) when MgSO 4 is given antenatally to women for seizure prophylaxis in preeclampsia or for neuroprotection. Taken together with our recently published data (Koning et al, 2017), we have now demonstrated that MgSO 4 provides preconditioning neuroprotection in four brain injury models (HI at PND 4 rat, PND 7 rat and PND 5 mouse as well as mouse PND 5 ibotenate lesion), supporting that this phenomenon is generalizable to some extent irrespective of species, type of insult and developmental age.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Additionally, the serum Mg 2+ concentrations measured in both models 3 h post injection were within the therapeutic window (2–4 mmol/L) when MgSO 4 is given antenatally to women for seizure prophylaxis in preeclampsia or for neuroprotection. Taken together with our recently published data (Koning et al, 2017), we have now demonstrated that MgSO 4 provides preconditioning neuroprotection in four brain injury models (HI at PND 4 rat, PND 7 rat and PND 5 mouse as well as mouse PND 5 ibotenate lesion), supporting that this phenomenon is generalizable to some extent irrespective of species, type of insult and developmental age.…”
Section: Discussionsupporting
confidence: 87%
“…The present results together with our previous report offers some mechanistic insights into how MgSO 4 protects the immature brain, i.e . it has to be given as a pre‐exposure at least ≥12 h prior to the insult (Koning et al, 2017) whereas MgSO 4 is often not effective if given just prior, during or after the insult (de Haan et al, 1997, Galvin and Oorschot 1998, Greenwood et al, 2000; Koning et al, 2017). We believe that MgSO 4 offers preconditioning, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations